Antimicrobial Activity of Senna siamea Fresh Leaf Extracts (Ethanolic and Aqueous Solution) on Shigella Species and Pseudomonas aeruginosa - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Usman Ikrimah; Onyemaechi, Eze Emmanuel; Paul, Shinggu Paula (Darul Yasin Al Sys, 2025)
The rising threat of antibiotic-resistant bacteria has intensified the search for alternative antimicrobial agents, particularly those derived from plants. Numerous plant species have long been used in traditional medicine, with leaf extracts showing promising antimicrobial potential. This study investigates the antimicrobial activity of ethanol and aqueous leaf extracts of Senna siamea against Shigella spp. and Pseudomonas aeruginosa. Fresh leaves of S. siamea were collected, authenticated, and subjected to solvent extraction using ethanol and distilled water. The antimicrobial effects of the extracts were evaluated using the agar well diffusion method, while the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined through standard microbiological procedures. The ethanol extract exhibited marked inhibitory effects against P. aeruginosa at all tested concentrations, whereas the aqueous extract showed greater efficacy against Shigella spp. at 100% concentration. Both extracts demonstrated bactericidal properties at a concentration of 1 mg/mL. These findings indicate that S. siamea contains bioactive compounds with significant antimicrobial activity, affirming its traditional use in treating infectious diseases. The results support the potential of S. siamea as a natural alternative for managing bacterial infections, particularly those involving resistant strains. Further research involving phytochemical profiling, toxicological analysis, and clinical evaluation is recommended to isolate the active compounds and assess their pharmaceutical applications.